1996
DOI: 10.1103/physrevb.53.12422
|View full text |Cite
|
Sign up to set email alerts
|

Percolative vortex motion in high-temperature superconductors

Abstract: A model for percolative vortex motion in inhomogeneous superconductors is introduced. Near the percolation threshold the linear, frequency-dependent electronic conductivity is found to obey scaling laws. The percolation model for vortex motion provides an alternative explanation to the experimental finding of scaling in the electronic conductivity that is conventionally attributed to a vortex glass transition. The critical exponents derived from simulations of bond percolation on three-dimensional lattices are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
(54 reference statements)
1
15
2
Order By: Relevance
“…12,13 Since the percolation transition is a second order phase transition, scaling of the E-J curves 10,11 and the linear conductivity () 12,13 is found near the percolation threshold p c that corresponds to the vortex-glass transition temperature T g . However, whereas the present author found universal scaling exponents for the linear conductivity in a lattice model, 12,13 Yamafuji and Kiss 10 and Matsushita et al 11 found nonuniversal scaling exponents for the E-J curves. In this work a lattice model for the calculation of voltage-current curves is introduced and it is shown that the E-J curves obey scaling relations containing only the universal critical exponents t and s known from the study of the linear conductivity of metal-insulator and metalsuperconductor mixtures.…”
contrasting
confidence: 54%
“…12,13 Since the percolation transition is a second order phase transition, scaling of the E-J curves 10,11 and the linear conductivity () 12,13 is found near the percolation threshold p c that corresponds to the vortex-glass transition temperature T g . However, whereas the present author found universal scaling exponents for the linear conductivity in a lattice model, 12,13 Yamafuji and Kiss 10 and Matsushita et al 11 found nonuniversal scaling exponents for the E-J curves. In this work a lattice model for the calculation of voltage-current curves is introduced and it is shown that the E-J curves obey scaling relations containing only the universal critical exponents t and s known from the study of the linear conductivity of metal-insulator and metalsuperconductor mixtures.…”
contrasting
confidence: 54%
“…Then, the vortices will pass through the weak links, connecting the normal phase clusters. In this case depinning has percolative character, 14,15 because vortices move through randomly generated channels. Weak links form readily in HTS's due to the intrinsically short coherence length.…”
Section: Vortex Dynamics In Percolative Superconductorsmentioning
confidence: 99%
“…During this process the vortices will first pass through the weak links, connecting the normal-phase clusters. In this case depinning has percolative character, 12,13,14 because unpinned vortices move through randomly generated channels created by weak links. Weak links form readily in HTS's due to the intrinsically short coherence length.…”
Section: Magnetic Flux Trapping and Depinning In Percolative Supercon...mentioning
confidence: 99%